2002
DOI: 10.1002/ccd.10157
|View full text |Cite
|
Sign up to set email alerts
|

Nondominant right coronary artery occlusion and ventricular tachyarrythmias

Abstract: It is usually considered that occlusion of a nondominant right coronary artery is not associated with significant consequences. We report two cases of nondominant right coronary artery occlusion that presented with sudden cardiac death. Timely intervention resulted in complete resolution of the ventricular arrhythmias. This highlights the need for greater vigilance in the recognition and treatment of these lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Moreyra et al reported ST elevation in both anterior and inferior leads [1] . Rao et al reported ST elevation in inferior leads associated with occlusion of NDRCA [2] . Our patient also had ST elevation in inferior leads.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreyra et al reported ST elevation in both anterior and inferior leads [1] . Rao et al reported ST elevation in inferior leads associated with occlusion of NDRCA [2] . Our patient also had ST elevation in inferior leads.…”
Section: Resultsmentioning
confidence: 99%
“…Moreyra et al reported a case of total occlusion of NDRCA resulting in isolated RV infarction and ventricular fibrillation [1] . Rao et al reported a case of recurrent ventricular fibrillation due to subtotal occlusion on NDRCA [2] . Vural et al reported a case of isolated RV infarction and severe tricuspid regurgitation due to occlusion of nondominant RCA [3] .…”
Section: Resultsmentioning
confidence: 99%